Cultural Values of Education at the Sumatra Thawalib Islamic Boarding School Parabek, Bukittinggi - Muhammad Fazis (Ta'dib, 2023)
This study aims to find the meaning and describe the management of organizational culture change in the educational environment at the Sumatra Thawalib Islamic Boarding School, Parabek. The research method used in this research is qualitative with the type of phenomenological study. The instrument in this research is the researcher himself. Data collection techniques are used in the form of in-depth interviews, participant observation, and documentation. The guarantee of the validity of the data is carried out by triangulation of sources and increasing the persistence of researchers in understanding each data obtained. The results showed that the management of organizational culture change in the educational environment at the Sumatra Thawalib Islamic Boarding School, Parabek Evidencettinggi is contained in the acronym "THAWALIB" which consists of (1) Taqwa; (2) himmah; (3) Ahl al-'ilmi wa al-'worship; (4) Wara'; (5) Trust; (6) Layin; (7) Istiqomah; (8) Birrul. The core values of the management of organizational culture change as stated in the eight core values are reflected in various aspects of life that exist in the Educational Institutions at the Sumatra Thawalib Islamic Boarding School, Parabek, Bukittinggi. The management of organizational culture change which is reflected in the acronym for the name of the Islamic boarding school is also the core values of how the educational institution is run to achieve the vision, mission, and goals that have been set.